Energy efficiency obligation schemes: their future in the EU - Fawcett, T; Rosenow, J; Bertoldi, P (Springer, 2018)
EU member states have been encouraged to introduce energy efficiency obligation schemes (EEOS) to help meet energy saving objectives. As a result, there are now 15 EU EEOS in existence, compared with just six prior to the introduction of the 2012 Energy Efficiency Directive. At the same time, the long-standing EEOS in Denmark and the UK have faced challenges because of concerns over increasing costs. This paper considers the role of EEOS in current and future EU and national policy. Firstly, this paper sets out in more detail the place of EEOS in EU energy policy. Then, the future of longer-established EEOS is explored, using Denmark and the UK as case studies. Recent and planned redesigns in these two countries are detailed, with analysis of the factors which led to changes in policy ambition. For new EEOS, key risks to delivery of savings are an over-ambitious delivery target and time line in the absence of policy learning opportunities. The policy risk for nine EEOS is assessed, with savings being most at risk in Croatia, Latvia and Spain. The paper concludes with an analysis of EEOS within the future policy mix. The discussion considers the place of EEOS in evolving EU policy, future savings from EEOS, their relationship with energy companies and the possible influence of different framings of energy efficiency. The continuing need for EEOS is explored, with concluding ideas about how to secure a strong and effective future for this policy tool.